Pengaruh Ekspor, Investasi, Inflasi Dan Pengangguran Terhadap Pertumbuhan Ekonomi Di Indonesia Tahun 1990-2020 - Angelita Titis Pertiwi; Ivonni Regina; Gatot Sasongko (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
This study analyzed the effect of export, investment, inflation, and unemployment to the constant gross domestic product (GDP) used to see the economic growth in Indonesia in 1990 to 2020. Time series data in this study are analyzed using ECM (Error Correction Model) to investigate the long-run and short-run effects of the independent variables, including export, investment, inflation, and unemployment, on GDP. The results suggest that there is no evidence to conclude that export affects GDP significantly in both long-run and short-run period. In terms of short-run period, investment gives positif effects on GDP, but inflation and unemployment are associated with negatif effects on GDP. Regarding long-run period, only investment and inflation significantly gives positive effects on GDP